Wetting of steel by Al 4043 alloys in cold metal transfer process. (August 2015) - Lin, Q.; Zhou, Y.; Cao, R.; Chen, J. H.
Abstract : The sessile drop method was used for the study of the wetting of steel by Al 4043 alloys in cold metal transfer process. The moving of triple line was determined by the reaction at interface rather than the wettability of reaction product. The evaporation of Zn coating for galvanised steel induced instability of wetting for small wire feed speeds and reduced the heat input in the interface. Wire feed speed dependent interfacial structures were observed, which are due to the heat input dependent interfacial reactivity. The calculation of adsorption energy can be used for the explanation of interfacial structures and Zn rich zone in Al galvanised steel system.